Consumer Protection Against Advertisements Prohibited from Broadcasting: Perlindungan Konsumen Terhadap Pariwara yang Dilarang untuk Ditayangkan - Hani Aisah Farah (Unnes Law Journal, 2012)
This study is purposed to identify the monitoring mechanism of advertisements broadcasted by Television Broadcasting Agent and consumer protection from advertisements which are not allowed to be broadcasted. This study uses qualitative research design with sociological juridical approach. The result of this study shows that monitoring mechanism towards advertisements broadcasted by Television Broadcasting Agent is run by two national agents. They are Lembaga Sensor Film who monitors advertisements before being broadcasted and Komisi Penyiaran Indonesia who monitors advertisements after being broadcasted, beside those two national agent, there is also an association named Badan Pengawas Periklanan Indonesia Persatuan Perusahaan Periklanan Indonesia.The monitoring run by those national agents is assumed as not totally successful and does not really protect consumers advertisements which are actually not allowed to be broadcasted. The different Regulation between the agents and the duties which are not maximum in monitoring advertisements is the causing factor of unprotected consumers towards advertisements which are not allowed tobe broadcasted by television broadcasting agent.